MENGATUR KELAHIRAN DALAM PERSPEKTIF MORAL KATOLIK - Yohanes Sudaryanto (Jurnal Teologi (Journal of Theology), 2015)
The Church believes that God calls human to become partner in the work of creation. He gives sex to human as a mean of the plan. Contraception is an instrument used by human for birth control. The Church, with her moral teachings doesnt forbid Catholic couples to control births, but she wants them to use the methods are that morally good. The study aims to determine the things that underlie Catholic couples in the Parish of St. Yusuf Pekerja Gondangwinangun Klaten in choosing specific ways to regulate births. To collect the data, the author used questionnaires to all respondents and in depth interviews to some of the respondents. The results indicated that the majority of Catholic couples use contraception to regulate births in their family. There are several factors that influence this practices. The main factor is their lack of complete knowledge about contraception and the Church's teaching about it. Based on the data, the author proposes some pastoral suggestions for the Church in order to guide the Catholic couple to regulate births. Delivering the Church's teaching on birth control is one form of responsibility of parish priests to keep the values of the Catholic marriage.